Approaches to the assessment of completeness and quality of the registry of exposed population offspring - S. A. Shalaginov; A. V. Akleyev (Радиационная гигиена)
Uncertainties of radiation risk of late radiation exposure effects in humans are to a great extent determined by completeness and quality of epidemiological data. The registry of the studied cohort is of fundamental importance for the cohort studies. Particular difficulties appear in the course of development of the exposed population offspring registry as these people in contrast to their parents were not affected by radiation exposure. The formation of the cohort of the exposed population offspring has its peculiarities and requires evaluation of its completeness and quality. The objective of this research is to study the value of the sex ratio as a possible criterion to assess the completeness and quality of the registry of the Techa River Cohort offspring. The register of descendants of the irradiated population at the end of 2019 included information on 25930 persons. The formation of the register of descendants of the population irradiated on the Techa River was started in the mid-1950s. At the same time, various documents were used to confirm the fact of birth of a child in irradiated persons. In the Techa River population the proportion of offspring with exposed mother and unexposed father is 22.2%, those with exposed father and unexposed mother made up 13.9%; the proportion of in utero exposed offspring is 44.6%. In accordance to the widely accepted published data it was to be expected that the number of male 1st-generation offspring in the cohort would be lower. However, the results of the conducted research show no changes in the sex ratio among offspring relative to the population-based control. Moreover, it was stated that the sex ratio in the population of the 1st-generation offspring of the exposed residents of the Techa River settlements should not be viewed as secondary. The assumption about the influence of the pre-conceptional exposure of the parents as well as that of the in utero exposure on changes in the sex ratio was not confirmed. It is shown that the decrease in the value of the sex ratio is associated with misreporting of the male 1st -generation offspring who died in childhood and at young age. The value of the sex ratio in groups formed based on the character and dose of exposure, depended mainly on the source of information used in the course of the offspring registry development.